Microbios y mosquitos en la emergencia de la medicina tropical en Brasil y Argentina - Sandra Caponi (Les Cahiers ALHIM)
I analyze how, in the late 19th and early 20th centuries, researchers from Brazil and Argentina addressed the problem represented by tropical diseases. There, it is possible to identify two opposed research programs. Even when Brazilian and Argentine hygiene were inheritors of the Pasteurian principles, Brazil faced its sanitary problems from a new approach that integrated microbiological studies with other knowledge, such as parasitology and entomology. Argentina, on the other hand, insisted on reducing all its sanitary problems to those that could be considered within a framework where microbiological studies were integrated with the strategies typical of classical hygiene. The distinction between these two research programs is linked to how the two international centers of reference, the Societé de Phatologie Exotique (1908) and The London School of Tropical Medicine (1898), approached the problem of tropical diseases that appeared in the overseas colonies. This historical moment allows us to observe how scientific research is articulated with the fear of otherness that the tropics and their inhabitants represented for the colonialist gaze.